Construction of houses from containers - Lacerda, Luiz Bento Panta; Carvalho, Márcio César de; Corgozinho, Marco Túlio; Paula, Lucas Davis Ribeiro de; Villani, Paulo Marcelo (PARAMÉTRICA, 2023)
The general objective of this research is to understand the possibilities of using containers as an innovative and sustainable construction system in the construction of houses. The methodology used here was that of a literature review, since books and articles by different authors were used to respond to the general objective proposed in this research. Thus, it is concluded that the construction of houses with containers is of total relevance for the environment as it also has economic viability for the builder. This type of construction is important for environmental sustainability and the reuse of this material, preventing it from being discarded in nature.